Verbal Memory Impairment in Patients with Subsyndromal Bipolar Disorder - Sumiyoshi, Tomiki; Toyomaki, Atsuhito; Kawano, Naoko; Kitajima, Tomoko; Kusumi, Ichiro; Ozaki, Norio; Iwata, Nakao; Sueyoshi, Kazuki; Nakagome, Kazuyuki (Frontiers in Psychiatry, 2017)
Backgrounds: Several domains of cognitive function, including learning memory and executive function, are impaired in mood disorders. Also, the relationship between disturbances of these two cognitive domain has been suggested. In line with the recent initiative to establish a standard measure of cognitive decline in bipolar disorder, the present study was conducted to 1) test the criterion-related validity and test-retest reliability of the California Verbal Learning Test (CVLT)-II Japanese version, and 2) determine if type of word learning tasks (i.e. with or without a category structure) affects severity of verbal memory deficits in patients with subsyndromal bipolar disorder. Methods: Thirty-six patients with bipolar disorder with mild symptoms and 42 healthy volunteers participated in the study. We first compared effect sizes for memory deficits in patients among the CVLT-II, Brief Assessment of Cognition in Schizophrenia (BACS), and Hopkins Verbal Memory Tests-Revised (HVLT-R). We next evaluated the correlations between scores of the CVLT-II vs. those of the BACS and HVLT-R. Bipolar patients were re-assessed with the same (standard) or alternate forms of the CVLT-II and HVLT-R one month later. Results: Scores on the CVLT-II 1-5 Free Recall and Long-delay Free Recall, as well as the HVLT-R Immediate Recall, but not the BACS List Learning were significantly lower for patients compared to control subjects. The effect sizes for cognitive decline due to the illness were comparable when measured by the CVLT-II and HVLT-R, ranging from 0.5 to 0.6. CVLT-II scores were significantly correlated with those of the HVLT-R and BACS. Test-retest reliability of the CVLT-II was acceptable, and no significant practice effect was observed when the alternate form was used. There was no consistent relationship between mood symptoms and performance on the CVLT-II. Conclusions: These results suggest the CVLT-II Japanese version is able to discriminate between bipolar disorder patients and healthy controls with good sensitivity and validity. Data in this study also indicate that the degree of verbal memory deficits in bipolar disorder may be influenced by memory organizational strategy.